Assessment of Heavy Metals in Sediment and Its Effect on Fish Near Jetty Sungai Bahru, Kuala Perlis - Syaza Afifa Abdul Rahim (School of Environmental Engineering, University Malaysia Perlis, 2015)
To determine the concentration of heavy metals in sediment and fish near jetty Sungai Bahru, Kuala Perlis. To determine the fish content are follow with the Malaysian Food Regulation 1985 requirement as food sources. To investigate the relationship between the concentration of heavy metals in sediments and its effects on fish.